PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA TEMA PRAJA MUDA KARANA DI KELAS III SD NEGERI 105327 PERDAMEAN - Angel A Marbun; Anton Sitepu; Juliana Juliana (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to determine the effect of the discovery learning model on student learning outcomes on the praja Muda Karana theme which was carried out in class III of SD Negeri 105327 Perdamean for the 2020/2021 academic year. There are 60 students in the class, all of them are in the third grade. Saturated sampling was used to collect samples from up to 60 students, who were divided into two groups of 30 and 30 students, respectively. An experimental approach was used in this investigation. The results of statistical analysis showed that the learning outcomes in the experimental class using the Discovery Learning model were in the good category, with an average of 83.2. Meanwhile, without using the control class learning model, learning outcomes were not significantly different from the KKM which was set at an average of 65.3. Because tcount > ttable, Ho is rejected and Ha is accepted by t-test, the value of tcount = 5.976 while t-table is 1.697. This shows that the discovery learning model has a significant effect on the learning outcomes of third grade students of SD Negeri 105327 Perdamean for the 2020/2021 academic year. Keywords: Learning Outcomes, Young Praja Karana, Discovery Learning Model